The effects of early or late multifetal reduction procedure on perinatal outcomes in multiple pregnancies reduced to twins or singletons: A single tertiary center experience. (March 2022) - Sarac Sivrikoz, Tugba; Demir, Omer; Kalelioglu, Ibrahim Halil; Has, Recep; Karakas Paskal, Ezgi; Kundakci Ozdemir, Pelin; Yuksel, Atil
Highlights: Multifetal reduction procedure has a favourable contribution to perinatal survival. Transabdominal approach may also be preferrable in early gestational weeks. Perinatal survival is more favourable in reduction to singletons than twins. The timing of the procedure may not be definitely decisive for perinatal outcomes. Abstract: Objective: The aim of the study was to compare the effect of early or late fetal reduction (FR) procedures on perinatal outcomes in multiple pregnancies reduced to twins or singletons. Study Design: This retrospective cohort study consisted of data from a single tertiary center between January 2013 and December 2020 and included 103 women with multiple pregnancies between 8 and 14 gestational weeks and who underwent FR by transabdominal approach. Late FR was defined as 11–13 6/7 gestational weeks (Group L) and early FR was defined as 8–10 6/7 gestational weeks (Group E) in the study. All pregnancies with FR were named Group S (Single) if reduced to singletons and Group T (Twin) if reduced to twin pregnancies. Results: Thirty four percent (n = 35) were reduced to single pregnancy, the remaining 66% of these cases (n = 68) were reduced to twin pregnancy. The overall survival rate was 90%.When the cases were examined in terms of pregnancy complications, it was observed that the PPROM rate and preterm labor rate in the Group T were statistically significantly higher than the Group S (p = 0.015 and p < 0.001, respectively). When comparing the overall survival results between Group S and Group T, it was found that the overall survival of Group S was statistically significantly better (p < 0.001). When Group E and Group L were compared in terms of their pregnancy course and neonatal outcomes, no statistically significant difference was found between them. No statistically significant difference was found between the complication rates in the first week after the procedure (p < 0.05). Neonatal intensive care need was found at a rate of 31% in those with Group E, while this rate was found as 39% in Group L, and this difference was also not statistically significant (p = 0.480). When the preterm labor rate was compared between these two groups, there was no statistically significant difference in all three subgroups (<32nd, <34th, and <37th gestational weeks). Conclusion: When FR to singleton is required for fetal or maternal reasons, it should be discussed with the parents that the risk of fetal loss is similar to FR to twins, but the effect on perinatal survival is more favorable than expected.